DIFFERENCES IN THE COMPETENCY RESULTS OF MIPA TEACHERS IN WEST SERAM AND EAST SERAM DISTRICTS TO INCREASE THE QUALITY OF EDUCATION IN MALUKU - Syafruddin Kaliky; Patma Sopamena (IAIN Ambon, 2020)
Teachers are one of the most important competences in an education system. Therefore, teacher competence can affect the quality of education. This study aims to determine the differences in the results of the mapping of professional and pedagogical competencies of Mathematics and Natural Sciences teachers in West Seram and East Seram Districts in improving the quality of education in Maluku through questionnaire data. This study used a survey research method with a sample of 25% of the MIPA teacher population in SBB and SBT districts, namely 42 Mathematics and Natural Sciences teachers in West Seram Regency and 25 Mathematics and Natural Sciences teachers in East Seram Regency. The results showed that: a) Professional competence of Mathematics and Natural Sciences teachers in SBB district is not different from the SBT district which is indicated by F count 0.05; b) The pedagogical competence of Mathematics and Natural Sciences teachers in SBB Regency is not different from SBT Regency which is indicated by F count 0.05, which is sig. Value = 0.262> 0.05.